(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
Asa result of Field Research in this article,the preservation of natural ecosystems, which are considered relevant today, and its delivery to the future generation, for this, as a result of our field research in the cemeteries of the city of Chirchik, Tashkent region, in 2022-2023, plants form various adaptations to the external environment during evolution, and as a result, their life forms